DIAGNOSTIC INFORMATIVENESS OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE ASSESSMENT TEST AND CONSEQUENCE OF INCORRECT EVALUATION OF THE FUNCTIONAL STATUS - Vyshnyvetskyy, I.; Kholopov, L.; Batashova-Halynskaya, V. (World of Medicine and Biology, 2016)
The aim of study was to assess the informativeness of chronic obstructive pulmonary disease (COPD) diagnostic test and the consequence of incorrect evaluation of the functional status due to the presence of concomitant chronic heart failure (CHF). 438 people with COPD were studied. CHF was found in 142 patients, 31.7% with low and 68.3% with preserved systolic function of left ventricle. Assessment of COPD-specific health status was conducted using the TOX index. Found that TOX results should be corrected downward in patients with concomitant CHF assigned to groups B and D with values TOX bordering diagnostic "cut-off point" in 10 points. Statistically significant differences in TOX levels were found between patients with and without CHF only in the D clinical group. The values on which TOX result should be reduced in patients with COPD in combination with CHF is in the range from 1 to 5.